Experimental investigation on the active thermal management of grooved flat heat pipe under the electrohydrodynamic effect. (February 2023) - Xin, Fei; Wang, Qiuwang; Yan, Yuying; Tian, Wenchao
Abstract: Grooved flat heat pipe (GFHP) is very promising to be utilized to cool high-heat-flux devices within limited space, but its performance is usually constrained by capillary limit. Electrohydrodynamic (EHD) technology with simple structure, low power consumption and flexible electrodes distribution is proposed to apply to the GFHP, aiming at realizing the active thermal management of GFHP. Visual and thermal experiments are carried out to investigate influences of fluid type, inclined angle, electric field intensity, electrodes distribution and grooves structure on the GFHP under the EHD effect. It is found that EHD force can weaken the demand of capillary suction for the GFHP and strengthen the heat and mass transfer process inside the GFHP, further increasing the heat transfer capacity and thermal conductivity of GFHP with low power consumption. And working fluid types, inclined angle, electric field, electrodes distribution and grooves structure can significantly affect the performance of GFHP. The application scope of heat pipe under negative inclined angle and working fluid with small surface tension are enlarged under the EHD effect. The thermal performance is optimum for the GFHP with V2 sloped convex gradient grooved wick and EHD effect adding to the whole section, which displays higher heat transfer capacity by 1.2 times and lower thermal resistance by 15.3% under 8 kV in comparison with V1 straight GFHP without EHD effect. However, under the EHD effect, the working fluid in the GFHP requires to possess high insulating property, small electrical conductivity, low saturation pressure and suitable electric field intensity to avoid breakdown. Highlights: Active thermal management of GFHP by EHD technology is put forward. Feasibility of working fluid in the GFHP under EHD effect is investigated. Influences like electric field intensity and electrodes distribution are analysed. Thermal performance of V2 sloped convex gradient GFHP with EHD effect is optimum.